Identification of Mooring and Unmooring Risks to Minimize Workplace Accidents on the MV. CTP Honor Using the Hierarchy Method - Riko Efendi Jaya Ramadhani; Damoyanto Purba; Ardhiana Puspitacandri; A.A. Ngurah Ade Dwi Putra Yuda (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Occupational safety during mooring and unmooring activities is an important aspect in ship operations because these activities have a high risk of accidents, especially due to snap-back hazards, work environment conditions, and human factors. This study aims to identify potential hazards, analyze the level of occupational accident risk using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method, and determine risk control measures in mooring and unmooring activities on board the MV. CTP Honour. The study uses a descriptive quantitative approach. The study population includes all mooring and unmooring activities and the crew involved, while the sample is focused on the crew's work activities in the deck area during the mooring and unmooring process. Data were collected through observation, interviews, and documentation, then analyzed using the HIRARC method. The results showed that there were 20 potential hazards consisting of 4 Extreme Risk categories, 11 High Risk categories, and 5 Medium Risk categories. The highest risks were found in activities related to mooring rope tension and the presence of crew in the snap-back zone area. The research conclusion shows that the implementation of risk control through increased supervision, implementation of safety meetings, use of PPE, effective communication, and compliance with SOPs can minimize the risk of work accidents during mooring and unmooring activities on board ships.